Complementary or Discrete Contexts in Online Indexing: A Comparison of User, Creator and Intermediary Keywords - Kipp, Margaret E. I. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This paper examines the context of online indexing from the viewpoint of three different groups: users, authors, and intermediaries. User, author and intermediary keywords were collected from journal articles tagged on citeulike and analysed. Descriptive statistics and thesaural term comparison shows that there are important differences in the context of keywords from the three groups. Cet article examine le contexte de l’indexation en ligne du point de vu de trois groupes : les usagers, les auteurs, et les intermédiaires. Les mots-clés des usagers, des auteurs et des intermédiaires tirés des articles de périodiques ont été étiquetés avec CiteULike et analysés. Les statistiques descriptives et la comparaison des termes thésauraux montrent qu'il existe des différences importantes entre le contexte des mots-clés provenant des trois groupes. ***Student to CAIS/ACSI Award Winner***